Spinal cord atrophy and myelomalacia following triple intrathecal chemotherapy in a patient of relapsed acute lymphoblastic leukemia - Agrawal, Sheesham; Sulaniya, Pawan Kumar; Garg, Kapil; Sitaraman, S; Sulaniya, Chandrakanta (Indian Journal of Child Health, 2016)
Paraplegia in a case of leukemia is an uncommon finding. It can be disease related, therapy related, or both. It may or may not be reversible or curable. Here, we are discussing an unusual acute life-threatening, therapy related condition, where triple intrathecal therapy in a relapsed acute lymphoblastic leukemia child led to severe spinal cord atrophy and myelomalacia causing acute paraplegia with urinary retention. Subsequently, the patient developed respiratory failure and succumbed to death. There is very few case reported of this complication. The aim of this case report is to sensitize, the pediatricians and pediatric oncologists about this life-threatening complication of chemotherapy.